PERBANDINGAN PERSEPSI SISWA KELAS AKSELERASI DAN NON AKSELERASI TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMA NEGERI 3 JOMBANG - MAURIN F, RULITA MAURIN (Jurnal Prestasi Olahraga, 2013)
Perception is the process of understanding and pass judgement in accordance with the experience and the vision also carries with it a parser-milahan to make a conclusion or opinion. Accelerated classes are educational service program that is given to students who have the potential and talent of exceptional intelligence to complete his studies ahead of the other students (regular). The non-accelerated class is a program of educational services provided to students with normal only or have the potential of a child has been registered and attend school, unchanged isn't as accelerated classes to complete his studies with a time that is already in the set. This research using methods descriptive quantitative namely granting poll that later in analysis using quantitative analysis which aims to know and describe perception students in a common the teaching in public sma 3 jombang that than 20 graders the acceleration and 29 class non acceleration. Based on the research comparison perception graders the acceleration and class non acceleration against learning education corporeal sport is as follows: that average value of the acceleration of 7.5, class while average value of a class of non acceleration of 7,27. It will assumed that comparison perception students between the class acceleration preferred by learning corporeal olaharaga education and the health of on class non acceleration. Keyword: comparison, perception, acceleration, non acceleration, penjasorkes